Nutritional Status of School Children and Efficacy of Awareness Intervention in Their Nutritional Knowledge – A Prospective Experimental Trial: Life Sciences-Nursing - B, Ranjitha; C H, Rajiny (International Journal of Life Science and Pharma Research, 2023)
Malnutrition is a severe health problem that impacts young children’s development and growth. An accurate measure of a child’s health is their nutritional state. Malnutrition affects a child’s ability to grow physically and mentally, weakens their immune system, and makes them more susceptible to infection. By 2030, one billion school-aged children will have developmental delays in their physical and mental health due to malnutrition, primarily undernutrition, which already affects more than 200 million children of school age. On the other hand, stronger immunity, better health, and increased productivity are all benefits of proper nutrition. The study’s main aim was to assess the nutritional status of school-going children belong Puducherry. The purposive sampling technique was done after the purposive sampling method. The 8-Interview schedule was administered to the selected 30 samples of middle school-going children in Puducherry. After a preliminary inquiry, an interactive awareness session was conducted. This program was conducted by the same team, which is well-versed in doing the same.Regarding the frequency and percentage of nutrition status, among middle school students, a majority (57 percent) of the 30 students interviewed suffered from underweight and cold intolerance. Forty-three percent of people were anemic, tired, have diffuse hyperpigmentation, and loss of appetite. Regarding other problems, 37 percent claimed to have lost their sense of taste. Twenty-five percent of students had an adequate intake of cereals, but the variety in cereal ingestion was rare. According to the analysis of the dietary assessment. 40 % of samples only had a good intake of pulses, 83 % had a poor intake of vegetables and green leafy vegetables, and most of the students were taking only less quantity of milk, nuts, fruits, egg, fish, and meat probably because they belong to a low economic category and a lack of awareness. On analyzing the type of exercise the selected samples did, frequent cycling (40 %), walking (17%), and a paltry 10 % participated in the sport. After the awareness session, the students gained adequate knowledge about nutritional status. Keywords: ,